Produksi Wacana Syiar Islam dalam Kitab Pegon Kiai Saleh Darat Semarang dan Kiai Bisri Musthofa Rembang - Munawir Aziz (Fakultas Agama Islam Universitas Muhammadiyah Yogyakarta, 2013)
This paper explores the shift in the da’wah concept taking place in the coastal area of Java by examining two manuscripts written by two notable figures in the 19th and 20th centuries, Kiai Saleh Darat from Semarang and Kiai Bisri Musthofa from Rembang. These two Islamic scholars are prolific writers and have penned a number of works in Arab- Pegon. Their writings have become references for Islamic students (santri) studying in traditional educational institutions in coastal areas of Java over decades. This paper attempts to answer the following questions: how the dakwah concept is conceived in the Kyai Saleh Darat’s and Kiai Bisri Musthfa’s works? How do their strategies in dakwah and the implementation shari’a influence the views of Islamic students and scholars in the coastal areas of Java? Why do we have to see coastal areas of Java as an instrument? From the narratives of Islamic historiography in Southeast Asia, coastal area of Java has an important position because it has become a node of the Islamic scholar networks. By utilizing the genealogical concept, this paper traces the roots and intellectual origin of the Javanese Islamic scholarship. Keywords: Java coastal areas, discourse production, da’wah, Islamic scholars, kiai Saleh Darat, kiai Bisri Musthofa.